FRI0513 Validating Mri-Detected Inflammation Thresholds Predictive of Structural Damage Progression in Patients with Rheumatoid Arthritis in A Randomized Placebo-Controlled Trial. (15th July 2016) - Ahmad, H.A.; Baker, J.F.; Østergaard, M.; Ye, J.; Emery, P.; Conaghan, P.G.
Abstract : Background: In rheumatoid arthritis (RA), the concept that subclinical inflammation causes damage progression is now well established, but there is little work on how much inflammation is safe. 1 A previous study established RA MRI Scoring (RAMRIS) synovitis and osteitis thresholds (≤3 each and ≤9 [≤3 plus 2*≤3] as a total inflammation score) that correlated with a low risk of structural damage progression. 2 Further validation of these thresholds may guide physicians in clinical practice more reliably to identify individuals with a low likelihood of structural damage progression. Objectives: To validate the performance of RAMRIS synovitis, osteitis and combined total inflammation thresholds in the prediction of structural damage progression. 1 Methods: AVERT (Assessing Very Early Rheumatoid arthritis Treatment) was a Phase IIIb, randomized, active-controlled, 24-month trial, with a 12-month, double-blind treatment period. Patients with early RA received abatacept + MTX, abatacept monotherapy or MTX. Contrast-enhanced MRIs of the dominant hand and wrist were performed. MRI data were pooled from all three treatment arms (intent-to-treat population) for this post hoc analysis. Inflammation (synovitis, osteitis and combined) and erosion were scored by two central readers at baseline, Month 6 and Month 12. Structural damage progression was defined as erosion change >0.5. Patients were stratified into "low" and "not low" risk groups for MRI structural progression based on their inflammation scores at the start of the observation period: low: ≤3 for synovitis, ≤3 for osteitis and ≤9 when combined (with osteitis double-weighted due to its strong correlation with progression), as suggested by Baker et al. 2 Log odds ratio of probability of progression were compared between subgroups. Results: 351 patients were randomized and treated, with MRIs at baseline; 276 (78.6%) and 235 (67.0%) also had MRI data available at Month 6 and Month 12, respectively. The percentage of patients with structural damage progression at follow-up was significantly higher in the "not low" versus "low" risk subgroup for all comparisons (Table ). The probability of progression from Month 6 to Month 12 was significantly lower among patients with synovitis score ≤3, osteitis score ≤3, and total inflammation score ≤9 at Month 6. Conclusions: The applied inflammation thresholds distinguished between patients with RA at lower or higher risk of structural damage progression, validating the previously proposed thresholds. This provides further support for the clinical value of measuring inflammation via MRI, as well as its role in predicting structural damage progression. References: Gandjbakhch F, et al. J Rheumatol 2014;41:398–406. Baker J, et al. Arthritis Rheumatol 2015; 67(Suppl 10):S832. Disclosure of Interest: H. A. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. F. Baker: None declared, M. Østergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Janssen, Merck, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer-Ingelheim, Celgene, Eli Lilly, Centocor, GSK, Hospira, Janssen, Merck, Mundipharma, Novartis, Novo, Orion, Pfizer, Regeneron, Schering-Plough, Roche, Takeda, UCB, Wyeth, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis, Samsung Bioepis, P. G. Conaghan Consultant for: AbbVie, Lilly, Novartis, Pfizer, Speakers bureau: AbbVie, Janssen, Roche